(untitled) (CIPEEX, 2024)
Arnica montana, commonly known as arnica or mountain tobacco, is a plant native to mountainous regions of Europe and North America that has played a significant role in the history of herbal medicine. With vibrant yellow flowers, the plant is recognized for its phytotherapeutic properties with valuable therapeutic applications, which are currently being extensively studied and acknowledged, even in pharmaceutical industries. To contribute to the construction of knowledge about the phytotherapeutic potential of arnica (Arnica montana). A narrative literature review was conducted to gain a deep understanding of the analyzed topic, presented as a summary for the moment. The research was based on critical analysis gathered from four scientific articles in Portuguese and four in English, along with a master’s thesis and a doctoral dissertation, both in Portuguese. These materials were obtained through searches on websites and institutional repositories, allowing for a comprehensive and up-to-date investigation. The meticulous analysis of these sources provided a solid foundation for the construction of this work, enriching it with relevant evidence and perspectives. Arnica montana, with a long history in this regard, is widely recognized for its medicinal properties and has become an increasingly important focus in the scientific and herbal medicine communities. According to the aforementioned authors, its therapeutic potential is noteworthy, particularly in terms of anti-inflammatory, analgesic, and healing properties. Clinical and laboratory studies, as well as updated literature reviews and meta-analyses, have demonstrated its efficacy in treating various conditions, including muscle pain, bruises, arthritis, and skin injuries. In studies conducted by researchers such as Kriplani, Guarve, and Baghael (2017) and Silveira et al. (2021), it is evident that the anti-inflammatory action of Arnica montana, attributed to compounds like helenalin, has been extensively studied and proven effective in reducing swelling and alleviating pain associated with traumatic injuries. Furthermore, its ability to accelerate the healing process makes it a valuable choice for the treatment of superficial wounds and bruises. Its anti-inflammatory, analgesic, and healing potential make it a valuable option for relieving various health conditions. However, according to these researchers, safety and proper usage should be priorities when incorporating arnica into therapeutic treatments, ensuring its maximum benefit. Through the consulted literature, it was observed that Arnica montana proves to be a valuable medicinal plant with a long history of therapeutic use. Its benefits, including relief from bruises, hematomas, and muscle pain, have made it an important resource in natural medicine. However, it is crucial to emphasize the importance of responsible use under proper guidance, as improper application or internal consumption may lead to undesired side effects. Continuous study of arnica, both in terms of effectiveness and safety, is essential to maximize its potential as a natural therapeutic option.